Study on spatiotemporal changes of ecosystem service trade-offs/synergies and driving mechanisms in the key zone of mountain-river-sea coupling: A case study of the southwest Guangxi Karst-Beibu Gulf - Chunlian Gao; Baoqing Hu; Zhenchuan Wang; Simin Huang; Lili Zhang (Ecological Indicators)
Understanding the spatiotemporal patterns and driving mechanisms of ecosystem service (ES) trade-offs/synergies is crucial for sustainable development and effective ES management in regions experiencing environmental pressures. This study examines the southwest Guangxi Karst-Beibu Gulf, a key mountain-river-sea coupling zone, to reveal these characteristics and mechanisms from 2000 to 2020. Using correlation analysis, geographically weighted regression, and geoprobe, we found that food production (FP), carbon storage and sequestration (CS), and habitat quality (HQ) decreased, sediment delivery ratio (SR) increased and then decreased, and water yield (WY) and nutrient delivery ratio (DR) exhibited opposite trends to SR. Spatially, CS and DR were lower in the central region, whereas WY and FP decreased from southeast to northwest, with HQ and SR exhibiting the opposite pattern. Vertically, FP decreased while other ecosystem services (ESs) increased. ESs in this region were predominantly synergistic, although trade-offs were observed between FP and CS, SR, and DR, particularly within the watershed key zone. Overall, trade-off/synergy areas decreased with increasing elevation with the most significant decrease observed in the Level-IV area. Interactions between precipitation, evapotranspiration, elevation, slope, soil, population density, and human activity index were the primary drivers influencing changes in trade-off/synergistic intensity. Effective ES management should consider these interacting factors to achieve an optimal and sustainable ES provision across the mountain-river-sea region.